2020
DOI: 10.1111/cgf.14023
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Models for Acquiring the Optical Properties of Translucent Materials

Abstract: The outset of realistic rendering is a desire to reproduce the appearance of the real world. Rendering techniques therefore operate at a scale corresponding to the size of objects that we observe with our naked eyes. At the same time, rendering techniques must be able to deal with objects of nearly arbitrary shapes and materials. These requirements lead to techniques that oftentimes leave the task of setting the optical properties of the materials to the user. Matching the appearance of real objects by manual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 232 publications
(282 reference statements)
0
22
0
Order By: Relevance
“…Although computer graphics is often used as a tool for studying translucency perception (e.g., Urban et al, 2019;Xiao et al, 2014), perceiving translucency and accurate reproduction of translucent appearance is itself an important topic for the computer graphics community, especially when photorealism is at stake (Frisvad et al, 2020). One of the most significant, yet challenging, topics is accurate rendering of the human skin, which not only plays an essential role in the movies, video games, and other segments of the entertainment industry, but also extends to the fields of computer vision (face detection and edge detection; Gkioulekas et al, 2015), medicine, and cosmetology (Igarashi et al, 2005;Li et al, 2018).…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although computer graphics is often used as a tool for studying translucency perception (e.g., Urban et al, 2019;Xiao et al, 2014), perceiving translucency and accurate reproduction of translucent appearance is itself an important topic for the computer graphics community, especially when photorealism is at stake (Frisvad et al, 2020). One of the most significant, yet challenging, topics is accurate rendering of the human skin, which not only plays an essential role in the movies, video games, and other segments of the entertainment industry, but also extends to the fields of computer vision (face detection and edge detection; Gkioulekas et al, 2015), medicine, and cosmetology (Igarashi et al, 2005;Li et al, 2018).…”
Section: Applicationsmentioning
confidence: 99%
“…One of the most significant, yet challenging, topics is accurate rendering of the human skin, which not only plays an essential role in the movies, video games, and other segments of the entertainment industry, but also extends to the fields of computer vision (face detection and edge detection; Gkioulekas et al., 2015 ), medicine, and cosmetology ( Igarashi et al., 2005 ; Li et al., 2018 ). Although considerable progress has been made in this direction, skin rendering , which inherently implies the accurate reproduction of translucent appearance, is a topic of active ongoing research ( d’Eon & Irving, 2011 ) and remains especially challenging owing to the multilayer nature of a human skin ( Frisvad et al., 2020 ; Nunes et al., 2019 ).…”
Section: Background and Motivationmentioning
confidence: 99%
“…This significantly limits the types of surfaces that one can faithfully model. An extensive body of work provides extension of this outset and models more advanced surface types and light scattering phenomena [FJM∗20]. An important extension is the use of explicitly defined microgeometry based on Kirchhoff theory [Kaj85].…”
Section: Related Workmentioning
confidence: 99%
“…The optical scattering distribution function is a topic of interest in engineering applications such as the manufacture of high-quality mirrors for scientific use [8], and knowledge of this topic has been supported by the development of infographics and surface rendering [9][10][11][12]. A number of theoretical approaches developed to model the bidirectional reflectance distribution function (BRDF) and the most complete bidirectional scattering-surface reflectance distribution function (BSSRDF) is presented in the review by Frisvad et al [13], which provides a comprehensive analysis of the approaches that can be found in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…2 of 13 where S q stands for the root mean square height of the surface topography, θ i is the incidence angle of the light on the surface, and λ is the light wavelength. Other models, based on the Beckmann-Kirchhoff theory, approximate the topography using a normal distribution of microfacets and are better suited to modelling the optical scattering produced by surfaces with roughness on the micro/milli scale [11,[15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%